Optimizing the Management of Cash Waqf at the Indonesian Waqf Board: A Normative Analysis Of Islamic Law and Law No. 41 Of 2004 - Yogisa Prastika Putri; Muttaqin Choiri; Ahmad Musadad (Al-Amwal : Journal of Islamic Economic Law, 2026)
Purpose  –  This study aims to analyze the optimization of cash waqf management at the Indonesian Waqf Board (BWI) through the perspective of Islamic law and Law Number 41 of 2004 concerning Waqf. The study focuses on assessing the effectiveness of cash waqf management and its conformity with both sharia principles and the national legal framework. Method –  This  research employs a normative-empirical legal approach. Normative data were obtained from Islamic legal sources, DSN-MUI Fatwa No. 2 of 2002, Law No. 41 of 2004, and Government Regulation No. 42 of 2006, while empirical data were collected through interviews, observations, and documentation at the Surabaya Representative Office of the Indonesian Waqf Board. The data were analyzed qualitatively using a descriptive-analytical method. Result – Empirical findings indicate that BWI Surabaya has implemented structured cash waqf collection and management programs, including community-based waqf initiatives and investment through sukuk instruments. However, several challenges remain, including limited nazhir capacity, low public literacy, weak institutional coordination, and limited innovation in productive waqf development. From the perspective of Islamic law, the management of cash waqf is consistent with the principles of maqāṣid al-sharī‘ah, particularly in preserving wealth and promoting public welfare. From the perspective of positive law, the implementation of cash waqf has complied with the provisions of Law No. 41 of 2004 and Government Regulation No. 42 of 2006 concerning waqf governance and management. Implication – Although cash waqf management at BWI is generally consistent with Islamic law principles and the provisions of Law No. 41 of 2004, its optimization requires strengthening institutional governance, improving nazhir professionalism, enhancing public literacy, and expanding digital-based innovation. These measures are essential to increase the effectiveness, accountability, and socio-economic contribution of cash waqf as a sustainable Islamic social finance instrument.